Determinants of foreign direct investment (FDI) inflow in China - Shaf'i, Hairiz Hanil (Faculty of Business Management, 2015)
Foreign Direct Investment can be defined as investment by one country into another and normally invest by foreign companies rather than governments. Foreign direct investment involves establishing operations or acquiring tangible assets, including stakes in other businesses. Foreign direct investment is seen as an important element for economic development in developing countries. By injecting the technology transfer from developed countries into developing countries. Besides that, FDI also influences domestic investment and stimulates improvements of human capital and institutions in the host countries. A country like China is one of the market players among other developing countries and had been known as one of the countries that received high FDI among other countries. However, in 2012, China’s economy turned down to be unstable. For that reason, this research is to determine which variables that stimulate the changes FDI in China. The determinants chose are the interest rate, exchange rate, inflation rate, Gross Domestic Product, and trade openness. The data will be collected from Data Stream, and World Bank Data for the range for the year 1983 - 2013. The analysis of the data will be done by using E-Views software, by a method Ordinary Least Square (OLS) regression, and the other data treatment in order to examine the level of significance of each proxy to FDI in China. By doing this research is expecting that the interest rate, exchange rate, inflation rate, Growth Domestic Product GDP), and trade openness will have a significant effect in influencing the level of China’s FDI.